Pengaruh Gaya Kepemimpinan dan Pengembangan SDM Terhadap Kinerja Karyawan PT. Ikapharmindo Putramas Medan - Zafitri, Amanda Alifah; Prayudi, Ahmad; Pribadi, Teddi (Mahesa Research Center, 2025)
This study aims to analyze the influence of leadership style and human resource development (HR) on the performance of employees of PT. Ikapharmindo Putramas Medan. The research sample consisted of 69 respondents using a saturated sampling technique, where the entire population was used as a sample. The data collection method was carried out through questionnaires, interviews, and literature studies, while data analysis used descriptive methods and multiple linear regression methods with a significance level of 0.05. The results of the F test show that leadership style and HR development simultaneously have a positive and significant influence on employee performance. The results of the determination coefficient (R²) test showed that the Adjusted R Square value was 79%, which means that leadership style and HR development contributed 79% to employee performance, while 21% was influenced by other factors not examined in this study. These findings confirm that leadership improvement and HR development programs are essential to optimize employee performance. PT. Ikapharmindo Putramas Medan is advised to improve leadership training and employee skills to support the company's growth.